1988
DOI: 10.1038/331533a0
|View full text |Cite
|
Sign up to set email alerts
|

Membrane currents that govern smooth muscle contraction in a ctenophore

Abstract: Ctenophores are transparent marine organisms that swim by means of beating cilia; they are the simplest animals with individual muscle fibres. Predatory species, such as Beroe ovata, have particularly well-developed muscles and are capable of an elaborate feeding response. When Beroe contacts its prey, the mouth opens, the body shortens, the pharynx expands, the prey is engulfed and the lips then close tightly. How this sequence, which lasts 1 s, is accomplished is unclear. The muscles concerned are structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 15 publications
2
14
1
Order By: Relevance
“…Secondly, the IA-like current is largely inactivated within 50 ms at plateau potential (about 90 % inactivated as steady state at -20 mV, K. Muraki, Y. Imaizumi & M. Watanabe, unpublished observation). Quite recently, it has been suggested that IA-like current in smooth muscle cells has a role in reducing the rate of decay of the afterhyperpolarization (Beech & Bolton, 1988;Bilbaut, Hernandez-Nicaise, Leech & Meech, 1988) as has been originally reported in molluscan neurones (Connor & Stevens, 1971). This mechanism was not examined in the present study.…”
Section: Y Imaizumi K Muraki and M Watanabecontrasting
confidence: 39%
“…Secondly, the IA-like current is largely inactivated within 50 ms at plateau potential (about 90 % inactivated as steady state at -20 mV, K. Muraki, Y. Imaizumi & M. Watanabe, unpublished observation). Quite recently, it has been suggested that IA-like current in smooth muscle cells has a role in reducing the rate of decay of the afterhyperpolarization (Beech & Bolton, 1988;Bilbaut, Hernandez-Nicaise, Leech & Meech, 1988) as has been originally reported in molluscan neurones (Connor & Stevens, 1971). This mechanism was not examined in the present study.…”
Section: Y Imaizumi K Muraki and M Watanabecontrasting
confidence: 39%
“…Electrical signaling in ctenophores is well developed, especially in non-neuronal conductive and locomotory systems (Bilbaut et al, 1988;Dubas et al, 1988;Horridge, 1965a). Ctenophores have more genes encoding ion channels than sponges and placozoans .…”
Section: Reviewmentioning
confidence: 99%
“…The muscle cells are supposedly derived from a type of mesenchyme cell in the mesoglea; they are segregated early in embryonic development and therefore can be considered as true mesodermal derivatives [separate from epidermis and gastrodermis (Burton, 2008;Derelle and Manuel, 2007)]. Some of them are giant and well characterized electrophysiologically (Anderson, 1984;Bilbaut et al, 1988;Dubas et al, 1988;Stein and Anderson, 1984). These muscles are used to control hydroskeleton tone, body shape and feeding, which might be original functions of muscle elements in animal ancestors.…”
Section: Ctenophores As Basal Metazoans Sister To Other Animalsmentioning
confidence: 99%
“…Although typical in hydromedusae, ring muscles are not known in other orders of ctenophores. Lobate ctenophores have muscular lobes, but they are unlike the muscle discovered in Thalassocalycida (Bilbaut et al 1988;Tamm and Tamm 1989;Seipel and Schmid 2005). This remarkable adaptation allowed thalassocalycids to evolve a much diVerent body plan from ctenophores in the Order Lobata, one that permits it to quickly engulf relatively large volumes of water and capture fast prey.…”
Section: Discussionmentioning
confidence: 99%